A 2-GHz quadrature hybrid implemented in CMOS technology. - Frye, R.C (IEEE Journal of solid state circuits)
We have derived a lumped-element circuit from its coupled line counterpart for a quadrature hybrid coupler. We discuss the uses, design, and characteristics of such circuits in CMOS technology. We show measured characteristics of an example 50-Ω 2-GHz coupler with 65 dB of image rejection, 22 dB of directivity, and a 4.7-dB noise figure.